Successful Treatment of Cryptosporidiosis in 2 Common Marmosets (Callithrix jacchus) by Using Paromomycin - Hahn, Nina E (American Association for Laboratory Animal Science, 2010)
Two pair-housed, 1-y-old common marmosets (Callithrix jacchus) had intermittent loose feces and weight loss for approximately 2 mo. Cryptosporidum parvum was identified by ELISA in the feces of both animals. CBC and blood chemistry values, including liver enzymes, were within normal range. Both marmosets were treated with the antibiotic paromomycin (15 mg/kg PO) twice daily for 28 d. Resolution of clinical signs coincided with treatment. Three follow-up samples, taken 2 wk apart after treatment was finished, were negative for cryptosporidium ELISA in both animals. Paromomycin should be considered for treatment of cryptosporidiosis in marmosets.